Dioscin Alleviates Cardiac Dysfunction in Acute Myocardial Infarction via Rescuing Mitochondrial Malfunction - Shen, Tianyu; Lyu, Dayin; Zhang, Mengping; Shang, Hui; Lu, Qiulun (Frontiers in Cardiovascular Medicine, 2022)
Myocardial infarction is the most severe cause for heart attack, leading to sudden death. Although angiography and stenting are currently widely performed, effective therapeutic drugs are still needed. Herein, we present that dioscin as a natural product has a therapeutic effect on infarcted hearts via mitochondrial maintenance. After dioscin treatment, cardiac dysfunction is alleviated and remodeling is prevented. Mechanistically, disocin maintains mitochondria function, reflecting from the maintenance of KREB cycle, and abolishing the accumulation of ROS production. In this way, dioscin is a potential therapeutic drug for infarcted hearts, indicating targeting at mitochondrial maintenance is therapeutic candidate for infarcted diseases.